The effectiveness of mediation in divorce proceedings in Religious Courts. - putri, ahlam dita (Maliki Interdisciplinary Journal, 2025)
Mediation is a mandatory step in divorce proceedings in Indonesia, as stipulated by Supreme Court Regulation Number 1 of 2016. Its primary goal is to provide disputing parties with an opportunity to resolve conflicts amicably and avoid further escalation. However, in practice, mediation is often perceived as a mere formality, failing to achieve its intended purpose. This article aims to analyze the effectiveness of mediation in divorce proceedings by identifying factors contributing to its success or failure. This study employs a qualitative method based on library research to explore theories, regulations, and mediation practices. The findings reveal that the low success rate of mediation is influenced by the strong desire of couples to divorce, prolonged conflicts, and psychological and cultural factors. On the other hand, the effectiveness of mediation also depends on the professionalism of mediators, public compliance, and the implementation of regulations. In conclusion, although mediation has a strong legal foundation, its effectiveness must be enhanced through improved mediator qualifications and public education on the importance of peaceful dispute resolution.